المذهب المالكي بإفريقية الأسباب، الخصائص، والمحن في الفترة ما بين القرن 2 - 5 هـ / 8 م - 11 م - بن الواعر, عواطف بنت سالم بن مبارك (Al-Qurtas, 2026)
المذهب المالكي بإفريقية الأسباب، الخصائص، والمحن في الفترة ما بين القرن 2 - 5 هـ / 8 م - 11 م